Morphological response of Cherok Paloh estuaries towards the occurrence of Typhoon Rai - Abd Rahman, MM (2023)
Erosion is an alarming issue that affects the livelihood of coastal communities and the natural habitat. The permanent loss of land can alter the suitability of an environment for a species to thrive. This study aims to illustrate the effect of extreme conditions induced by Typhoon Rai, that occurred on the 11 to 21 December 2021, along the Cherok Paloh estuaries which is also a known breeding habitat for the Horseshoe Crab (Tachypleus gigas). Both XBeach and Delft 3D were implemented in this study as to simulate the impacts and extreme conditions induced by Typhoon Rai. XBeach, a coastal response model developed to simulate the nearshore and coastal processes as a 2-HD open-source process, which includes shore wave propagation, sediment transport, flow and bathymetry changes. The event is tested using the 1D model, and the sensitivity analysis is done using the error indicator of Brier Skill Score (BSS). The sensitivity was tested using various morphological parameters of facua, wetslp and dryslp, which then has been compared with the final beach profile to calculate the BSS. This in turn, is replicated to the other 1D profile of Cherok Paloh Beach. When the default values of said parameters were used, the simulation indicated an overestimation in erosion volume. As per the result obtained from the BSS, the best model was obtained by changing the calibration parameters of facua and wetslp